Narasi Pembunuhan Anak Dalam Al-Qur’an (Studi Komparatif Tafsĭr Anwār At-Tanzĭl Wa Asrār At-Ta’wĭl Dan Tafsir Al-Jāmiʻ Li Aḥkām Al-Qur’ān) - Mubarok; Lizamah (Prodi Ilmu Al Qur'an dan Tafsir, 2025)
In the Qur’an, there are several verses that discuss the issue of child murder. Among the verses selected by the author are Surah Al-An’am [6]:151, Surah Al-Isra’ [17]:31, and Surah At- Takwir [81]:8-9. This research is centered around four main questions: 1. How does Al-Qurthubi interpret the verses about child murder? 2. How does Al-Baidhawi interpret the verses about child murder? 3. What are the similarities between the interpretations of Al-Qurthubi and Al-Baidhawi regarding the verses about child murder? 4. What are the differences between the interpretations of Al-Qurthubi and Al-Baidhawi regarding these verses? The aim of this study is to explore and understand the interpretations as well as to identify the similarities and differences between Al- Qurthubi’s and Al-Baidhawi’s interpretations concerning the verses that discuss child murder. This study uses a qualitative method based on library research. The data collection technique in this study is literature-based, meaning that the objects of study are obtained from library sources such as books, journals, articles, and other materials that support the research. Therefore, the data collection method used is literature review, and the data analysis technique is descriptive- comparative. The conclusion of this study is: both Al-Qurthubi and Al-Baidhawi in their commentaries explain that killing children—whether male or female—due to fear of poverty or while being in a state of poverty is prohibited (haram) and is considered a major sin. Al-Qurthubi explains in his tafsir that Ibn Abbas said: “During the pre-Islamic period of ignorance (jahiliyyah), if a pregnant woman was close to giving birth, she would dig a hole. If she gave birth to a girl, she would throw the newborn into the hole and cover it with soil; but if she gave birth to a boy, she would keep him.” There is a slight difference between Al-Qurthubi’s and Al-Baidhawi’s interpretations of the verses on child murder. Al-Qurthubi provides a more detailed explanation in his commentary. He also holds the opinion that practicing ‘azl (coitus interruptus—ejaculating outside the woman’s body) is comparable to child murder, as both involve the prevention of a living being or lineage. However, taking a human life is a graver sin and a worse act overall. Keywords: Child Murder, Comparative, Interpretation of Anwar al-Tanzil wa Asrar al- Ta’wil and Al-Jāmi’ li Aḥkām al-Qur’ān